Health Status of Elderly People Living in Old Aged Homes in Pokhara - Dhungana, Ananta Raj; Dhungana, Parbati (Journal of Karnali Academy of Health Sciences, 2020)
Background: Health is serious matter for the elderly people especially living in old aged homes. In this context, this study has tried to explore the health status of elderly people living in old aged homes.Methods: Information were collected from fifty seven elderly people living in purposively selected three major old aged homes of Pokhara by using structured questionnaire through interview techniques. The elderly people, who were unable to speak, hear, complete the interview process, have severe psychiatric disorder, did not have verbal consent to participate were excluded from the study. Descriptive analysis was carried out for this research.Results: Majority (87.7%) of the respondents had chronic physical health problem like back pain problem as major followed by other musculoskeletal problems, gastrointestinal disease, hypertension, respiratory problem, diabetes mellitus, heart disease, eyes and ears problem. The proportion of female was higher than male regarding their chronic physical health problem. Majority went to hospital when they were sick. Half of the respondents were worried about economic insecurity followed by lack of social relation, lack of treatment during illness, fear of future, lack of recreational activities, food management of old age homes, environment of elderly official, sitting and sleeping environment of elderly home and others respectively. All the respondents prayed god to cope with these stress followed by listening to religious hymns, go to religious places, solitary living, crying alone, and take cigarettes/alcohols.Conclusions: Health status of elderly people living in old aged home was not good since most of the elderly were suffered from chronic physical health problem. Females are more vulnerable.